Antimicrobial susceptibility of staphylococci isolated in canine pyoderma in Coro, Venezuela - Monzant López, Glenda (2019)
This retrospective investigation was focused on the study of the etiology of pyoderma in canines from the city of Coro (Falcón state, Venezuela), between 2010 and 2014, as well as the profile of antimicrobial susceptibility of staphylococcal bacteria. The most frequently isolated microorganism was Staphylococcus (pseud)intermedius, followed by Staphylococcus aureus and other species. Additionally, several multi-resistant isolates were detected for the two species mentioned, which did not correlate with cases of recurrent pyoderma. No significant association was detected between the recurrent pyoderma and risk factors such as the racial pattern, sex, age and infecting bacterial species. In general, isolated staphylococcal species showed significant (p<0.05) susceptibility to carbapenems, aminoglycosides and fluoroquinolones, and resistance to penicillin, cyclins, inhibitors of folate synthesis and polypeptides.